2011
DOI: 10.1097/iop.0b013e31821e9f5d
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Dimensions of the Lacrimal Gland in Normal Caucasian Orbits

Abstract: This study presents a normal range of Caucasian lacrimal gland dimensions seen on CT. Lacrimal gland size decreases with age, and no gender difference exists. This range can aid in differentiating diseased and nondiseased lacrimal glands, especially when correlated with physical examination. This may be useful in clinical trials that involve lacrimal gland size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 8 publications
3
36
1
Order By: Relevance
“…Studies both performed with MRI and CT reported a decrease in the lacrimal gland sizes with increasing age [5,6,13]. Also, in our study, there was a negative correlation between age and gland dimensions and volume.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Studies both performed with MRI and CT reported a decrease in the lacrimal gland sizes with increasing age [5,6,13]. Also, in our study, there was a negative correlation between age and gland dimensions and volume.…”
Section: Discussionsupporting
confidence: 65%
“…The other dimensions were variable. The coronal length was longer and axial and coronal widths were shorter than that observed by Tamboli et al, in a Caucasian population [6]. According to the study of a Korean population, the axial width was equal with the right orbits but smaller in the left in our study [11].…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The size of the lacrimal gland decreases with age but does not vary by gender [ 40 ]. The orbital lobe is the larger of the two lobes and lies posterior to the orbital septum and preaponeurotic fat and anterior to the levator aponeurosis [ 38 ].…”
Section: Secretory System Lacrimal Gland and Accessory Glandsmentioning
confidence: 99%